Critical notice of A new environmental ethics: life on Earth in the next millennium, 2nd edition - Rolston, Holmes, 1932-2025, author (Colorado State University. Libraries, 2020)
Critical notice of citations of Rolston's published book A New Environmental Ethics: Life on Earth in the Next Millennium. Covers both first and second editions.